The Influence of the Characteristics of Mathematical Outdoor Activities in Mobile Environments on Students’ Emotions - Daher, Wajeeh M. (International Journal of Interactive Mobile Technologies (iJIM), 2012)
This research attempted to find out how the characteristics of outdoor activities carried out with the mobile phone influence students’ emotions. The research findings point at the following components related to the activity as influencing students’ emotions: The activity novelty, the activity theme (related to everyday life, related to a new subject related to the students themselves or to an issue or a subject that the students like to do, etc.), the activity conditions (its physical part is easy/uneasy to perform, resources are available, etc.), the outer environment conditions (hot, warm, cold, etc.), the roles which the activity enables (these roles may or may not satisfy a student), the learning method enabled in the activity (exploring mathematical ideas independently, exploring mathematics collaboratively, etc.), the challenge or competition associated with the activity (it needs persistence, attention, etc.). These components show that taking care of students’ leaning emotions in outdoor mathematical activities can be achieved through paying attention to different aspects of the activity which are outlined above.